THE CURRENT SITUATION OF SEARCHING FOR BEAUTY CARE INFORMATION OF WOMEN LIVING IN VIETNAM (Vietnam Journal of Community Medicine, 2026)
Objectives: This study aimed at describing the current situation of searching for beauty care information of women living in Vietnam.Subjects and methods: A cross-sectional study was conducted on 258 Vietnamese women who were surveyed online in April 2022.Results and conclusions: Sources of information search through social networking sites such as Facebook (75.6%), YouTube (55.4%), Website (53.5%) were used the most. Accounted for 80.1% of the respondents who agree that finding beauty care information on the Internet was easy. Young people and people who know how to use social networks (87.1%) were the leading factor that helps to better access information about beauty care services. Besides, reference information from family members and friends were also an important source of information. Advertising activities, price, geographical location of beauty care services were also important factors affecting the process of searching for beauty care information.
Keywords: Beauty care, Vietnamese women, searching for information.